Ruthenium-catalyzed Aromatic meta-C-H Nitration of 1,2,4-thiadiazoles - Wang, Kai; Xu, Wenjing; Zhang, Pengfei; Cao, Xian-Ting (Current Organic Chemistry, 2022)
Aim and Objective: To develop a ruthenium-catalyzed method to prepare metanitration containing 1,2,4-thiadiazoles with potential biological activity. Moreover, the current protocol should exhibit a relatively broad substrate scope and functional group compatibility. Materials and Methods: The best condition for the synthesis of nitration containing 1,2,4- thiadiazoles derivatives was carried out employing a mixture of 0.20 mmol of 1 (1a: 47.6 mg, 1b: 53.2 mg, 1c: 70.1 mg, 1d: 59.7 mg, 1e: 81.2 mg, 1f: 54.8 mg, 1g: 61.4 mg, 1h: 74.8 mg, 1i: 53.2 mg, 1j: 59.0 mg, 1k: 54.9 mg, 1l: 50.0 mg), Cu(NO3)2•3H2O (120.8 mg, 0.5 mmol), Ru3CO12 (9.6 mg, 7.5 mol %), TBAOAc (18.0 mg, 30 mol %), AgTFA (66.2 mg, 1.5 equiv), oxone (123.0 mg, 1.0 equiv), DCE (1.0 mL) placing in a Schlenk tube and stirred at 90 oC under air atmosphere for 36.0 h. Results: A series of 1,2,4-thiadiazoles containing compounds with potential biological activity were prepared in yield ranging from moderate to good under mild conditions, exhibiting a relatively broad substrate scope and functional group compatibility. Conclusion: We have developed a ruthenium-catalyzed 1,2,4-thiadiazoles-assisted regioselective meta-C-H nitration of arenes. This study provides a simple and efficient approach for synthesizing 1,2,4-thiadiazoles derivatives, yielding the nitration products in moderate to good yields. A mechanistic study indicated that a radical pathway might be involved in this transformation.
Keywords: 4-thiadiazoles